2020
DOI: 10.1021/jacs.9b12530
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Aluminum Ions at the Mica Water Interface Links Hydrolysis State-to-Surface Potential and Particle Adhesion

Abstract: When hydrolyzable cations such as aluminum interact with solid–water interfaces, macroscopic interfacial properties (e.g., surface charge and potential) and interfacial phenomena (e.g., particle adhesion) become tightly linked with the microscopic details of ion adsorption and speciation. We use in situ atomic force microscopy to directly image individual aluminum ions at a mica–water interface and show how adsorbate populations change with pH and aluminum activity. Complementary streaming potential measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 54 publications
4
40
0
1
Order By: Relevance
“…[13][14] Similarly, electrokinetic measurements on both mineral colloids and surfaces in the presence of divalent or trivalent ions have yielded positive zeta potentials at a pH where the surfaces should be negative. 2,4,11,[15][16] The driving force for overcharging has been attributed to either "physical" interactions like ion-ion/ion-site correlations and dispersion forces (favoured by physicists) or "chemical" interactions that involve the formation of specific surface complexes (favoured by chemists). 8,12,[17][18] However, separating the effects of such physical or chemical interactions has proven particularly difficult for mineral oxides and multivalent ions based on the tendency of the latter to form different hydrolyzed species at higher pH.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14] Similarly, electrokinetic measurements on both mineral colloids and surfaces in the presence of divalent or trivalent ions have yielded positive zeta potentials at a pH where the surfaces should be negative. 2,4,11,[15][16] The driving force for overcharging has been attributed to either "physical" interactions like ion-ion/ion-site correlations and dispersion forces (favoured by physicists) or "chemical" interactions that involve the formation of specific surface complexes (favoured by chemists). 8,12,[17][18] However, separating the effects of such physical or chemical interactions has proven particularly difficult for mineral oxides and multivalent ions based on the tendency of the latter to form different hydrolyzed species at higher pH.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the surface potential of mica reverses from negative to positive with increasing pH due to specific adsorption of hydrolyzed species (Al(OH) 2+ and Al(OH)2 + ). 16 Another method that is intrinsically surface selective and sensitive to molecular speciation is the second-order non-linear optical technique vibrational sum frequency spectroscopy (VSFS). VSFS has been extensively used to investigate the amount of ordered water at the silica/water interface, [25][26][27][28][29][30][31] which can be used to report on the interfacial potential within the electric double layer.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) can image single ions adsorbed at various solid-liquid interfaces 7,17,30,33,[48][49][50] . One of the main advantages of the technique is its ability to probe individual ions in-situ but with local contextual information about the interface over tens of nanometres at the point of measurement 7,30,48,50 .…”
Section: Real-time Tracking Of Ionic Nano-domains Under Shear Flow Clodomiro Cafolla and Kislon Voïtchovsky *mentioning
confidence: 99%
“…Additionally, key effects, such as water molecules dissociation, pH and mobility 39,41 , are difficult to account for. Experimental approaches such as X-ray reflectometry [42][43][44][45] and neutron scattering 46,47 can probe the interface exchange dynamics, but they average over hundreds of thousands of ions and can be limited in their time resolution.Atomic force microscopy (AFM) can image single ions adsorbed at various solid-liquid interfaces 7,17,30,33,[48][49][50] . One of the main advantages of the technique is its ability to probe individual ions in-situ but with local contextual information about the interface over tens of nanometres at the point of measurement 7,30,48,50 .…”
mentioning
confidence: 99%
See 1 more Smart Citation